PENGARUH PENERAPAN METODE PROBLEM SOLVING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI SEKOLAH DASAR NEGERI 02 KOTO BARU KABUPATEN DHARMASRAYA - Fitria Sari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The IPS is a combination of social sciences which includes history, geography, sociology, anthropology, economics, politics and other. The merger of these social sciences is the teacher in demand to be able to teach creatively the model, media and learning methods are good and interesting so that the purpose of learning is achieved and get a value above the KKM that has been specified this research is in the background by still low ability of students in IPS subjects so that researchers are interested to see if the use of the problem method solving affect the outcome of students learning outcomes IPS in public elementary school 02 Koto Baru Dharmasraya District. This type of research is an experimental research, this study used pre-experimental design type one group Pretest-posttest design. The population in this study is all grades IV Students elementary School 02 Koto Baru Dharmasraya District. Samapel in this study was taken using a sampling technique or a saturated sample. Data collection techniques are taken by using the Pretests and posttest poll, then calculated using the SPSS 20 software. The results of this study are calculated based on non-parametric tests, it can be seen that Asym sig. (2-tailed) is worth 0.000 smaller < 0.05, it can be concluded that the hypothesis is acceptable. It means that there is a difference between the results of pretests and posttes, so that it can be concluded that the hypothesis is that there is a influence of the use of the problem solving method of learning outcomes in IPS in the subjects of State Elementary School 02 Koto Baru Dharmasraya.